Embedded structure energy storage integrated composite material and preparation method thereof
Through the design of sandwich structures and embedded energy storage units and sensing units, the problems of insufficient multi-directional load adaptability and safety management of existing structural energy storage composite materials under complex working conditions are solved, efficient energy storage and intelligent management are achieved, and the overall performance and functional integration of the material are improved.
Patent Information
- Application Number
- CN202510915331.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-10-03
AI Technical Summary
Existing structural energy storage composite materials have poor adaptability to multi-directional loads under complex working conditions, the battery cell connection method lacks the ability to automatically switch configurations, safety management is insufficient, the material system does not take into account both electrical insulation and impact toughness, and no intelligent sensor network is integrated, resulting in insufficient overall performance and functional integration.
A composite board with a sandwich structure is embedded with energy storage units and sensing units, and electrical connections and intelligent chip management are achieved through flexible circuits. Combined with honeycomb/grid insulation core materials and gradient thickness design, an integrated sensor network is used for real-time monitoring and intelligent management.
It improves the load-bearing performance and stability of the structure under multi-directional loads, realizes dynamic management and safe isolation of energy storage units, enhances electrical insulation and impact toughness, has self-sensing capabilities, and improves the safety and service life of the system.
Smart Images

Figure CN120749304A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials and electric energy storage, and in particular to an embedded structure energy storage integrated composite material and a preparation method thereof. Background Art
[0002] With the development of aerospace, electric vehicles, and portable devices, lightweight structures and high energy density are becoming parallel demands. In traditional designs, the load-bearing structure and energy storage components, such as batteries, are separated, increasing the weight and volume of the system. To improve efficiency, the concept of structural energy storage composites has emerged. These integrate energy storage devices, such as batteries or supercapacitors, directly into the load-bearing structure, achieving a multifunctional "structure as battery" integration.
[0003] Some designs have attempted to embed batteries into composite structures. For example, U.S. Patent US20160330842A1 discloses a structural energy storage component. This component creates an array of openings in a layer of electrically insulating material, embeds multiple energy storage devices, and then superimposes load-bearing composite layers on top and bottom, creating a multifunctional sandwich structure capable of withstanding tensile and compressive loads while also storing energy. This type of structural battery achieves a certain degree of weight efficiency. However, existing technologies still have several shortcomings: First, the structural design often uses a flat plate with uniform thickness, which is not adaptable enough to multi-directional loads under complex operating conditions, and the overall structural stability needs to be improved. Second, the battery cells are typically connected in a fixed series or parallel configuration, lacking the ability to automatically switch configurations based on operating conditions. This makes it difficult to isolate a cell in the event of a failure, and safety management is insufficient. Third, the material system often uses traditional combinations such as carbon fiber and epoxy resin, which do not adequately balance electrical insulation and impact toughness, and lacks a more integrated process between the functional and load-bearing layers. Fourth, intelligent sensor networks have not yet been effectively integrated into the structure, making it impossible to monitor the health of the structure and batteries in real time. It can be seen that how to introduce new structural designs, electrical connection architectures, material combinations and sensing functions into structural energy storage composite materials to further improve their mechanical properties, safe and intelligent management capabilities and functional integration is a technical problem that needs to be urgently solved in this field. Summary of the Invention
[0004] The object of the present invention is to provide an embedded structure energy storage integrated composite material and a preparation method thereof, so as to solve the above technical problems.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an embedded structure energy storage integrated composite material, which is composed of a composite plate with a sandwich structure and an energy storage unit and a sensing unit embedded therein;
[0007] The composite board includes a functional layer, a load-bearing layer and a surface layer;
[0008] The functional layer includes an electrically insulating inner core, a plurality of independent energy storage units are embedded in the internal pores of the electrically insulating inner core, a bearing layer is arranged on both sides of the electrically insulating inner core, and the outer side of the bearing layer is a surface layer;
[0009] The energy storage units are electrically connected via embedded flexible circuits, which are arranged along the surface and / or inside of the electrically insulating inner core, connecting the electrodes of each energy storage unit and integrating a smart chip;
[0010] The sensing unit is a sensor network arranged inside the composite material, and the sensor network is obtained by connecting sensors, flexible circuits and smart chips.
[0011] Furthermore, the electrically insulating inner core is in a honeycomb or grid shape.
[0012] Furthermore, the load-bearing layer is a laminated structure, including a fiber layer and a resin matrix;
[0013] The surface layer is a laminated structure, including a fiber prepreg layer or a fiber fabric layer.
[0014] Furthermore, the materials of the electrically insulating inner core, the fiber layer, the fiber prepreg layer and the fiber fabric layer independently include one or more of carbon fiber, aramid fiber and basalt fiber;
[0015] The resin matrix includes one or more of polyimide resin, FEP resin, epoxy resin and polyester resin.
[0016] Furthermore, the sensing unit is used to collect structural stress, strain distribution, vibration impact events or parameters of each energy storage unit.
[0017] Furthermore, the sensor network is arranged inside the panel, near the energy storage unit and at the structural connection part;
[0018] The sensor includes one or more of a MEMS piezoelectric sensor, a temperature sensor, a humidity sensor, a voltage sensor and a fiber grating sensor.
[0019] Furthermore, the smart chip includes a functional circuit of a battery management system and an optical fiber sensing module, which are used to detect the status of the energy storage unit and implement energy management strategies and safety measures.
[0020] The present invention provides a method for preparing the above-mentioned embedded structure energy storage integrated composite material, comprising the following steps:
[0021] Step 1) preparing an electrically insulating inner core and embedding the energy storage unit therein and fixing it;
[0022] Step 2) Arrange the flexible circuit and smart chip and integrate their electrical connection network on the electrically insulating core or panel;
[0023] Step 3) Lay out the panels and embed the sensors between the designated layers during assembly;
[0024] Step 4) The composite materials are laminated and assembled, and then cured and formed to obtain an integrated structural energy storage composite plate. After post-processing, an embedded structural energy storage integrated composite material is obtained.
[0025] Beneficial effects of the present invention:
[0026] Structural Innovation and High Load-Bearing Capacity: The use of a honeycomb / grid insulating core embedded within the energy storage unit, combined with a sandwich interlayer and gradient thickness design, ensures excellent load-bearing performance and stability under all-directional loads. Compared to traditional uniform sandwich structures, this innovative structure exhibits higher stiffness and strength under multi-directional loads such as bending, shear, and impact. It can be locally thickened for reinforcement or thinned for weight reduction as needed, achieving scenario-adaptive optimization.
[0027] Energy Integration and Intelligent Management: The innovative flexible circuit + intelligent chip architecture enables dynamic series and parallel switching and refined management of energy storage units. This means that the same structural board can adjust output characteristics according to the operating mode, such as parallel output to increase current when high power demand is high, and series connection to increase voltage when high voltage demand is high. If a battery cell fails or performance deteriorates, the system automatically isolates and replaces the circuit to prevent failure of the entire group. The integrated energy management system ensures balanced operation of each unit, significantly improving the safety and service life of the energy storage system.
[0028] Material synergy and functional integration: Through the optimized combination of multiple fibers and resins and a co-curing process, a high degree of synergy in mechanical properties, electrical insulation, and environmental tolerance is achieved. Carbon fibers and other materials provide high strength and high modulus, aramid fibers provide insulation and impact toughness, and basalt fibers provide heat and fire resistance. The combination of thermoset and thermoplastic resins imparts both rigidity and a degree of toughness to the structure. The functional layers are firmly bonded at the microscopic level, avoiding delamination and interfacial stress concentration, thus achieving the integration of "structure + energy storage + insulation" functions and broadening the application boundaries of composite materials.
[0029] Intelligent Perception and Safety Monitoring: The embedded sensor network enables the structure to be self-aware, enabling real-time monitoring of structural loads and battery status. When the structure is subjected to unexpected impact or overload, sensors capture strain and vibration signals to promptly assess whether internal damage has occurred. When the battery experiences abnormal heating or leakage, temperature and humidity sensors immediately issue an early warning. Combined with algorithmic analysis by the intelligent chip, the integration of structural health monitoring (SHM) and the battery management system (BMS) is achieved. This not only improves operational safety (such as early detection of thermal runaway risks and the implementation of load reduction or power outage measures), but also provides data support for subsequent maintenance, extending product life.
[0030] High safety and reliable application: The honeycomb / grid isolation structure not only plays a load-bearing role, but also naturally acts as a fireproof partition between battery cells: even if a battery cell thermally runs away and catches fire, the surrounding insulating honeycomb walls will surround and isolate it, effectively preventing the flames from spreading to adjacent cells and improving the overall accident resistance. In addition, the structure of the present invention reduces additional components such as independent battery boxes and brackets, simplifies the system configuration, reduces weight and reduces failure points. Overall, this composite material has broad application prospects in aerospace structural power supplies, vehicle body structural batteries, wearable device casings, etc., and can significantly improve the system's integration and performance indicators, realizing industrial value. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a cross-sectional schematic diagram of the structural layers of the composite material described in Example 1.
[0032] Figure 2 This is a cross-sectional schematic diagram of the structural layers of the composite material described in Example 2.
[0033] Figure 3 This is a cross-sectional schematic diagram of the structural layers of the composite material described in Example 3.
[0034] Figure 4 This is a cross-sectional schematic diagram of the structural layers of the composite material described in Example 4.
[0035] Figure 5 This is a cross-sectional schematic diagram of the structural layers of the composite material described in Example 5. DETAILED DESCRIPTION
[0036] The present invention provides an embedded structure energy storage integrated composite material, which is composed of a composite plate with a sandwich structure and an energy storage unit and a sensing unit embedded therein;
[0037] The composite board includes a functional layer, a load-bearing layer and a surface layer;
[0038] The functional layer includes an electrically insulating inner core, a plurality of independent energy storage units are embedded in the internal pores of the electrically insulating inner core, a bearing layer is arranged on both sides of the electrically insulating inner core, and the outer side of the bearing layer is a surface layer;
[0039] The energy storage units are electrically connected via embedded flexible circuits, which are arranged along the surface and / or inside of the electrically insulating inner core, connecting the electrodes of each energy storage unit and integrating a smart chip;
[0040] The sensing unit is a sensor network arranged inside the composite material, and the sensor network is obtained by connecting sensors, flexible circuits and smart chips.
[0041] In the present invention, the energy storage unit is electrically connected through an embedded flexible circuit. The flexible circuit board is arranged along the surface or inside of the inner core, connects the electrodes of each energy storage unit, and integrates a miniature smart chip. The smart chip contains the functional circuit of the battery management system and the optical fiber sensing module, which is used to monitor the voltage, temperature and other conditions of each energy storage unit. Through this intelligent management system, the series or parallel connection configuration of the energy storage unit can be automatically switched as needed to achieve dynamic adjustment of the output voltage and capacity; when a unit fails, the circuit can quickly isolate and bypass it to avoid the spread of the fault. At the same time, the smart chip executes energy management strategies, including actively balancing the charge state of each unit, optimizing the charge and discharge power distribution, and has fault diagnosis and early warning functions.
[0042] In the present invention, the electrically insulating inner core is preferably in a honeycomb or grid shape.
[0043] In the present invention, the sandwich structure and thickness gradient design of the composite plate enable the structure to have targeted strength and stiffness in different areas to meet multi-directional and multi-working load requirements and improve the overall structural stability and deformation resistance.
[0044] In the present invention, the load-bearing layer is a laminated structure, including a fiber layer and a resin matrix;
[0045] The surface layer is a laminated structure, including a fiber prepreg layer or a fiber fabric layer.
[0046] In the present invention, the materials of the electrically insulating inner core, the fiber layer, the fiber prepreg layer, and the fiber fabric layer independently include one or more of carbon fiber, aramid fiber, and basalt fiber;
[0047] The resin matrix includes one or more of polyimide resin, FEP resin, epoxy resin and polyester resin.
[0048] In the present invention, the carbon fiber composite layer provides high stiffness and strength, the aramid fiber layer provides electrical insulation and impact resistance, and the basalt fiber layer provides heat resistance and cost advantages. Through a reasonable lamination sequence and thickness gradient design, a multi-layer structure including a surface layer, a load-bearing layer, and a functional layer is formed.
[0049] In the present invention, the sensing unit is used to collect structural stress, strain distribution, vibration impact events or parameters of each energy storage unit.
[0050] In the present invention, the sensor network is arranged inside the panel, near the energy storage unit and at the structural connection position.
[0051] In the present invention, the sensor includes one or more of a MEMS piezoelectric sensor, a temperature sensor, a humidity sensor, a voltage sensing node and a fiber grating sensor.
[0052] In the present invention, a flexible sensor network is deployed inside the composite material to achieve real-time perception of the status of the structure and energy storage units, forming a structural health monitoring system. Through intelligent algorithm analysis, structural damage (such as delamination and cracks) or battery anomalies (such as overheating and leakage) can be detected in a timely manner, and corresponding safety measures (such as reducing local loads and disconnecting faulty batteries) can be implemented.
[0053] In the present invention, the smart chip includes a functional circuit of a battery management system and an optical fiber sensing module, which is used to detect the status of the energy storage unit and implement energy management strategies and safety measures.
[0054] The present invention provides a method for preparing the above-mentioned embedded structure energy storage integrated composite material, comprising the following steps:
[0055] Step 1) preparing an electrically insulating inner core and embedding the energy storage unit therein and fixing it;
[0056] Step 2) Arrange the flexible circuit and smart chip and integrate their electrical connection network on the electrically insulating core or panel;
[0057] Step 3) Lay out the panels and embed the sensors between the designated layers during assembly;
[0058] Step 4) The composite materials are laminated and assembled, and then cured and formed to obtain an integrated structural energy storage composite plate. After post-processing, an embedded structural energy storage integrated composite material is obtained.
[0059] In the present invention, in step 4), the curing process used for the curing molding is preferably a co-curing molding process or a staged curing process.
[0060] In the present invention, the temperature and pressure of the curing process are preferably such as to ensure that the energy storage unit is not damaged and the composite material is fully cured.
[0061] In the present invention, in step 4), the post-processing includes interface installation, sealing protection and function debugging.
[0062] In the present invention, different material layers and embedded energy storage units, flexible circuits, etc. are solidified and formed at one time, so that strong chemical bonds are formed between the layers, avoiding layered interface problems and ensuring the integrated fusion of structure and function. This combination design takes into account both electrical insulation and mechanical properties.
[0063] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0064] Example 1
[0065] In this embodiment, high-modulus carbon fiber and low-temperature curing epoxy resin are used as the faceplate and load-bearing layer materials. The upper and lower carbon fiber composite layers are each made of five layers of carbon fiber prepreg, each with a thickness of 1.5 mm. The upper and lower insulating layers are each made of thin glass fiber. A 15 mm thick aramid paper honeycomb with a hexagonal cell inner diameter of 19 mm serves as the electrical insulation core. Thirty-two 18650 lithium-ion battery cells, each with a capacity of 2000 mAh and a nominal voltage of 3.7 V, charged to 50%, serve as the energy storage element. Carbon fiber was chosen for its high specific strength and stiffness, significantly improving the structural load-bearing capacity. The epoxy resin matrix easily impregnates the fibers and has a mature curing process, providing a secure bond between the honeycomb core and the carbon fiber layers. The aramid honeycomb core is lightweight, insulating, and heat-resistant, accommodating batteries while maintaining structural stability. The high energy density and commercially mature 18650 cylindrical lithium battery cells make them suitable for embedded energy storage. This material combination achieves excellent mechanical properties while ensuring electrical safety.
[0066] Figure 1 This is a flat sandwich structure with an embedded structural energy storage integrated composite material. From top to bottom, its structure consists of an upper carbon fiber composite layer 1, an upper surface insulating layer 2, a honeycomb core 3, a lower surface insulating layer 5, and a lower carbon fiber composite layer 6. The cells of the honeycomb core 3 are arranged in a regular hexagonal grid, with battery cells 4 evenly distributed across the length and width of the board. A flexible circuit board 7 is arranged on one side of the honeycomb core 3. A micro temperature sensor 9 is embedded near the battery cells 4, and a thin-film piezoelectric sensor 10 is embedded in the center of the upper carbon fiber composite layer 1.
[0067] Based on the battery arrangement, a flexible printed circuit board (FPC) 8 is fabricated using copper foil traces and a polyimide substrate. This circuit includes a series-parallel switchable circuit for connecting the positive and negative terminals of all the batteries, a voltage divider sampling circuit for measuring the voltage of each battery cell, an NTC temperature sensor interface, and an STM32 series microcontroller chip with analog-to-digital (ADC) sampling and communication capabilities. The fabricated FPC is affixed to the sides of the honeycomb core 3, ensuring that the reserved solder points on FPC 8 align with the positive and negative terminals of each battery cell 4 where they will be placed. The microcontroller chip and related components are soldered to one end of FPC 8 to form a management module. Thin wires are then used to connect the communication and power interfaces to the outside of the board.
[0068] Insert the battery cells 4 one by one into the cells of the honeycomb core 3, ensuring that the top positive pole and bottom negative pole of the battery cell 4 contact the corresponding metal springs on the FPC 8. To ensure a secure connection, apply a small amount of conductive glue between the pole cap of each battery cell 4 and the spring of the FPC 8. Fill the gap between the battery cell 4 and the pore wall of the honeycomb core 3 with a circle of thermally conductive silicone pads to secure the position of the battery cell 4 and promote heat transfer to the honeycomb core 3. After completion, check that all battery polarity and circuit connections are correct to ensure there is no risk of short circuits.
[0069] Lay the lower panel carbon fiber composite layer 6 in a clean mold, cover its upper surface with a lower surface insulation layer 5, and then firmly place the honeycomb core material 3 assembly with embedded battery cells 4 and FPC 8 on the lower surface insulation layer 5, aligning the positions. Lay the upper surface insulation layer 2 on the upper surface of the honeycomb core material 3, embed the micro temperature sensor 9 near several battery cells 4, and attach it to the upper surface insulation layer 2. Then lay the upper panel carbon fiber composite layer 1, and place the thin film piezoelectric sensor 10 in the middle layer of the upper panel. Ensure that the sensor leads are extended to the edge of the board and connected to the sensing port of FPC 8. After all lamination is completed, cover it with peel-off cloth and porous isolation film to prepare for curing.
[0070] The assembled laminate was placed in a vacuum bag, evacuated to -0.08 MPa, and then placed in an autoclave. A low-temperature curing epoxy resin system was used, and the laminate was cured for four hours at 80°C and 0.3 MPa. The laminate was then cooled to room temperature in the oven and the cured composite panel was removed.
[0071] Trim excess resin and material from the edges of the board, ensuring that the circuit leads are exposed for easy connection. Power the flexible circuit management chip, connect it to the host computer, and test each battery channel. Burn the battery management software to monitor and control the 32 battery cells4, including: measuring the voltage and temperature of each cell, balancing charging, controlling the MOSFET matrix to switch between series and parallel modes, and setting a fault isolation strategy to disconnect cells if they are abnormal. Place the board in an environmental test chamber to simulate performance at different temperatures and ensure that the chip and sensor are functioning properly. Finally, apply an insulating and waterproof coating to the board surface for protection, and install a socket as a standard electrical interface to connect to the external circuit.
[0072] The size of the structural battery panel prepared in this embodiment is 1000mm×500mm×20mm, and the mass is about 5.0kg. The 32 embedded 18650 lithium battery cells are connected in a 4-series and 8-parallel configuration, which can provide a nominal voltage of 14.8V, a rated capacity of 16Ah, and a total energy storage of about 236Wh. Mechanical performance tests: In the three-point bending test, a concentrated load of 1kN was applied under the condition of a span of 800mm. The deflection at the center of the plate was only 5.2mm, and no delamination or damage occurred. Compared with the hollow sandwich plate of the same structure without embedded batteries, the bending stiffness was increased by about 15%, mainly because the bending moment of inertia increased after the honeycomb holes were filled with batteries. The compression test showed that the in-plane compressive buckling load of the structural plate reached 35kN, and local crushing first occurred in the non-battery hole area of the honeycomb core, and the overall structure remained stable. In terms of electrical performance, at room temperature and at a discharge rate of 0.2C (3.2A), the panel's output voltage dropped steadily from 16.8V (fully charged) to 12V (90% discharged) without abnormalities, and the continuous output power was approximately 50W. When high current is required, switching to parallel mode can support short-term pulse discharges of up to 160A (20A per parallel group), with a total peak power of up to 3kW, and the entire panel did not burn or fail. Experimental results show that the structure of this embodiment not only provides considerable energy storage, but also has good load-bearing mechanical properties and safety management capabilities. Compared with the traditional "structure + battery" separation solution, it is approximately 20% lighter, reflecting the significant advantages of the integrated structural energy storage design.
[0073] Example 2
[0074] In this embodiment, Kevlar fiber cloth and polyimide resin are selected as the panel materials. The electrically insulating core material is a hybrid structure of PEI foam and carbon fiber mesh. The energy storage unit is a high-power-density supercapacitor, with specifications of 2.7V, 100F, and a small module with a diameter of 30mm and a height of 50mm. The upper and lower panels are formed by five layers of Kevlar fiber fabric impregnated with polyimide resin. The thickness of the panels varies from 2mm at the thick end to 1mm at the thin end. This embodiment focuses on impact resistance and environmental resistance. Aramid fiber cloth and polyimide resin are selected as the panel materials. The core material is a hybrid structure of PEI (polyetherimide) foam and carbon fiber mesh. The energy storage unit is a high-power-density supercapacitor. Kevlar fiber, as an aramid fiber, has excellent toughness and impact resistance, and its inherent insulation and non-conductivity can avoid electrochemical coupling problems. Polyimide resin is resistant to high temperatures and radiation, making it suitable for use in harsh environments. Supercapacitors have high power density and rapid charge and discharge. Using them as energy storage elements can provide the structure with short-term high-power output capabilities. By combining this material with energy storage solutions, the requirements for high-temperature vibration resistance and transient energy supply of structural parts in scenarios such as aircraft engine compartments and rail transit can be met.
[0075] like Figure 2 As shown, the insulating core material has a zoned composite structure. In the thicker areas, the insulating core material is a PEI rigid foam block 12 with 12 cylindrical holes arranged in 4 rows x 3 columns. Each hole houses a cylindrical supercapacitor unit 13. A thin-film temperature sensor 17 is attached to each supercapacitor unit 13. Flexible circuits 15 are laid on both sides of the core material to connect the supercapacitor units 13. Four supercapacitor units 13 are connected in series, and three groups of supercapacitor units 13 are connected in parallel. The other end of the flexible circuit 15 is integrated into a management module 16 with a microcontroller. In the thinner areas of the insulating core material, the insulating core material is a carbon fiber reinforced grid 14, which does not house the energy storage unit but only provides support. A fiber Bragg grating strain sensor 18 is integrated into the carbon fiber reinforced grid 14. The resulting composite material is 20 mm thick at one end and 10 mm thick at the other.
[0076] A CNC machine tool is used to process circular holes with a diameter of 32 mm and a hole spacing of 50 mm on a PEI foam board according to the designed array to obtain a thick-end PEI rigid foam block 12. Pre-stretched and trimmed carbon fiber bundles are laid between the pores along the length and width directions of the PEI rigid foam block 12 to form a grid reinforcement. Then, a PEI resin adhesive is used to coat the interface between the carbon fiber bundles and the foam, and the reinforced honeycomb / grid hybrid core material is obtained by solidification. The carbon fiber reinforced grid 14 is manufactured by 3D printing. A wedge-shaped frame with a grid groove is printed using a high-performance thermoplastic resin (PEEK). The carbon fiber bundles are embedded in the groove and solidified to form a gradient core material that matches the size of the thick-end foam core material. The PEI rigid foam block 12 and the carbon fiber reinforced grid 14 are then spliced and glued at the gradient transition to obtain an overall electrical insulation core material blank with a gradient thickness.
[0077] The flexible circuit 15 is designed according to the layout of the supercapacitor unit 13. Its functions include: connecting wires for each of the four capacitors in series, parallel buses between groups, voltage monitoring points, capacitor balancing discharge resistors, and a microcontroller circuit. Considering the large operating current of the supercapacitor, the FPC uses 70μm thickened copper foil to reduce resistance. The FPC is attached to the upper and lower surfaces of the PEI rigid foam block 12 respectively, and fixed with a small amount of PI resin glue to ensure that each capacitor solder point is accurately located next to the hole position. The lead-out pole of the supercapacitor unit 13 is welded to the corresponding pad of the FPC (the upper side is connected to the positive pole and the lower side is connected to the negative pole). After welding, the capacitor unit is inserted into the foam hole (the reserved hole diameter is slightly larger than the capacitor diameter to place the adhesive). High-temperature resistant flame-retardant silicone is injected between the outer wall of each capacitor and the hole wall to fill the gap to fix the capacitor and provide a buffer. The temperature sensor 17 is attached to the top of each capacitor and the lead is connected to the sensing interface of the FPC. The fiber Bragg grating strain sensor 18 is pre-buried inside the carbon fiber reinforced grid 14 (laid in together during printing), and the fiber lead end is protected and ready for connection. After completion, the microcontroller management module 16 is installed on the side of the core material and connected to the FPC.
[0078] Prepare multiple sheets of Kevlar fiber cloth / PI resin prepreg at the thick end and thin end respectively. Since aramid fiber cannot be detected by electromagnetic methods like carbon fiber in terms of ply direction, marking lines are used here to ensure that the fiber direction conforms to the design. First, lay several layers of the lower surface aramid prepreg in the mold, and gradually transition the number of layers so that the thick end area is stacked with 6 layers and the thin end is stacked with 4 layers. Then put in the gradient core material blank with integrated capacitors and circuits (its lower surface has been coated with a layer of PI adhesive to bond the lower panel). Also apply a layer of adhesive on the upper surface of the core material, and then lay the upper surface aramid prepreg, with the number of layers corresponding to the lower surface layer. Keep the optical fiber path of the optical fiber sensor smooth during the entire assembly process, and lead out the lead-out end through the small hole on the side. Then, hot-press co-curing is performed: considering that the curing temperature of PI resin is relatively high (BPAA type polyimide is used in this example, with a curing temperature of 220°C), and the supercapacitor unit can withstand a temperature of about 85°C, a staged curing process is adopted. First, it is cured at 120°C and 0.2MPa for 2 hours to allow the prepreg to reach initial curing and the capacitor adhesive to cure. Then, the pressure is released to remove the plate, and the supercapacitor unit 13 is removed from the hole. The plate is then placed at 220°C and heated without pressure for 4 hours to complete the post-curing reaction of the polyimide resin. After cooling, the supercapacitor unit 13 is reinserted into its original position and fixed with a clamp or glue. This "thermal step-by-step" process ensures that the composite material layer is fully cured and avoids high-temperature damage to the capacitor element.
[0079] Reinstall the removed supercapacitor unit 13, check that all electrical connections and sensor circuits are intact, and package the fiber Bragg grating sensor's lead-out optical fiber and optical communication interface module.
[0080] The entire panel underwent environmental simulation testing: Under cyclic temperatures of -40°C to 80°C and random vibration conditions, the strain feedback from the fiber Bragg grating strain sensor (FBG) was measured to verify that the structure was free of cracks or looseness. High-speed video was used to observe the interface between the foam and the panel at different temperatures, confirming no debonding. Electrical performance testing was performed: the supercapacitor module was charged to a rated voltage of 10.8V, triggering the management module to balance the voltage of each series cell within ±0.05V. Discharging at a maximum current of 10A, while monitoring the temperature sensor, revealed that the temperature rise of each capacitor did not exceed 8°C, indicating effective heat dissipation. Transient power testing was conducted using a high-current electronic load. Under a 0→100A step discharge, the voltage drop of the capacitors in the panel was less than 0.5V, indicating no abnormal structural vibration. Finally, the integrated fiber optic sensing and temperature data were uploaded to the management module, enabling on-the-go monitoring.
[0081] The composite material plate of this embodiment has 12 supercapacitors embedded in the thick end area (20mm thick), with a total weight of approximately 4.8kg, of which the structural part is approximately 4.2kg and the capacitors and circuits are approximately 0.6kg. Mechanical properties: The gradient thickness design gives the plate high bending stiffness near the thick end, while the thin end saves weight. After a three-point bending test simulating the wing fixing method, when the thick end was subjected to a downward concentrated load of 800N, the maximum strain appeared near the thin end support. The fiber Bragg grating measured a strain of approximately 300με, and the plate did not damage. The overall equivalent bending moment stiffness is approximately 25% higher than that of the uniform thickness design, indicating that the gradient structure effectively reduces stress concentration. After the impact test (50J drop hammer impact on the center of the thick end), the aramid panel only produced slight indentations and no cracks, demonstrating its excellent impact toughness. Electrical performance: The supercapacitor module can be charged from 0 to 10.8V in 5 seconds (current limited to 20A condition), the instantaneous discharge current can reach more than 100A, and the continuous output power peak is approximately 1kW (maintained for several seconds). In scenarios where sudden power is required, such as instantaneous power supply of aircraft starting motors or emergency traction of rail vehicles, this structural plate can stably provide short-term high power and quickly recharge. In a high-frequency vibration environment (5g random vibration), the circuit connection is reliable and there is no breakage. In summary, Example 2 demonstrates the adaptability of the present invention in high-toughness, high-power density applications. The structure can provide fast charging and discharging capabilities as a "power plate" while meeting the load-bearing requirements, and has stable performance in harsh environments.
[0082] Example 3
[0083] In this embodiment, basalt fiber and unsaturated polyester resin are selected as the main materials. The electrical insulating core material is a 3D-printed partition network frame, and the energy storage unit is a flat lithium-ion polymer battery (soft-package battery) with a capacity of 5000mAh. The surface layer is a basalt fiber fabric layer obtained by compounding three layers of basalt fiber fabrics. The surface layer is 3mm thick and the surface layer is coated with a conductive coating. This embodiment is aimed at cost-sensitive application scenarios that require large-capacity energy storage (such as fixed energy storage components or general industrial equipment housings). Basalt fiber is inexpensive, heat-resistant and corrosion-resistant, and is an electrical insulator. Its mechanical properties are between carbon fiber and glass fiber, which can provide sufficient strength while reducing material costs; unsaturated polyester resin is easy to cure and mold at room temperature and is suitable for mass production. Lithium polymer batteries (referred to as "lithium battery packs") have high energy density and flat shape, and can cover a large area to provide electrical energy. This material combination can achieve low-cost manufacturing of large-scale structural energy storage components.
[0084] like Figure 3As shown, the composite material is a rectangular plate-like structure with a multi-cell compartmentalized layout. The electrically insulating core is a 3D-printed lattice frame 19 made of ABS plastic. The lattice frame 19 is 10mm thick and internally divided into 4 rows x 3 columns, totaling 12 cells. The cell walls are 2mm thick, and each cell is precisely sized to accommodate a battery cell 20 measuring 100mm x 80mm x 8mm. Basalt fiber fabric layers 21 flank the lattice frame 19. The lattice frame 19 is internally equipped with reinforcing ribs and wiring troughs. The battery cells 20 in each cell are connected to adjacent cells via flexible conductors. Ultimately, all cells are connected in a 3-in-parallel x 4-in-series arrangement to form a battery pack. Battery management modules 22 are located at the corners of the basalt fiber fabric layers 21.
[0085] An industrial FDM 3D printer was used to print a honeycomb lattice frame 19 made of ABS material. Pre-printed wiring holes and sensor slots were created on the walls of adjacent lattices to facilitate subsequent wiring. After printing, the frame was post-processed (support removal and burr removal). An epoxy primer was then applied evenly to the inner surface of the frame and allowed to cure naturally to improve adhesion to the fiber surface.
[0086] Twelve battery cells 20 are placed sequentially into the individual cells of the lattice frame 19 according to the designed polarity. Each cell is pre-coated with a layer of FEP film for insulation protection (to prevent contact with the resin and moisture intrusion). Adjacent cells are welded together using flexible silicone insulated wire, with three cells connected in parallel per row and four cells connected in series per column. Wires are threaded through routing holes in each cell wall, connecting between columns in series and within rows in parallel. Ultrasonic welding is used to reduce contact resistance. The positive and negative leads of all cells are connected together to the battery management module 22, which is then installed (including the overcharge and over-discharge protection circuitry and the balancing module). Simultaneously with welding, a thermistor is attached to the cell surface and soldered with a thin wire to the temperature monitoring port of the management module, allowing each cell to be monitored. To verify the seal, a small strip of color-changing silicone is placed in several corner cells. Its color can be observed through a transparent observation window to determine if water has entered. After all the internal components are installed, the front and back surfaces of the lattice frame 19 are temporarily covered with ABS cover plates to prevent overflow into the cavity during subsequent resin pouring.
[0087] The outer surface of the frame is pre-wrapped with a layer of release cloth, and then a layer of basalt fiber fabric 21 is laid on top, covering the entire panel area and extending 5cm beyond the edges. This is repeated on both the upper and lower surfaces. Vacuum bags are then placed around the edges, with injection and vacuum ports installed. Unsaturated polyester resin glue is prepared (adding 1.5% cyclohexanone peroxide curing agent to reduce the viscosity to 300 cP). The resin is then infiltrated into the basalt fiber fabric layers 21 on both the upper and lower surfaces through the injection ports under vacuum. The resin gradually cures at room temperature (2 hours for gelation and 24 hours for cure), forming a strong composite panel that is bonded to the lattice frame 19. The release cloth is removed, and any excess fiber trimmings are trimmed to create a smooth basalt fiber composite surface. At this point, the ABS cover that temporarily sealed the cells is removed. Since the resin has cured, a sealed wall forms where the panel meets the frame, securely enclosing the batteries. A sealing cover is also installed in the reserved opening at the battery management module 22 to facilitate subsequent maintenance and battery replacement.
[0088] A polyurethane coating containing conductive carbon black was sprayed onto the outer surface of the basalt fiber fabric layer 21, forming a 50μm-thick conductive shielding layer. This layer not only serves as an electromagnetic shield, but also, through a detection circuit connected to the battery management module 22, monitors the leakage current between the shielding layer and the battery's negative terminal in real time. (If insulation damage causes a small leakage current, an alarm will be triggered.) The mounting plate edge sealing strips and bolt hole bushings are installed to secure it as a device cover. The management module is connected to the external main control system, and the information of the 12 battery cells 20 is registered in the software. Finally, the entire structure was functionally tested, including insulation resistance testing (shielding layer resistance between each battery polarity >100MΩ), airtightness testing (no bubbles after 2 hours of submersion in water, no discoloration of the internal humidity indicator), and vibration testing (electrical connection stability under random vibration of 1grms), all of which met the requirements.
[0089] The basalt fiber composite energy storage material prepared in this embodiment has a size of 1000×500mm, a total thickness of 12mm, and a mass of approximately 8.5kg (of which the total weight of the battery is approximately 3kg, accounting for 35%). Structural performance: Through finite element simulation and experimental verification, the energy storage material can withstand a point load of 200N in the center under the condition of peripheral bolt fixing without a deflection of more than 3mm, meeting the general chassis cover stiffness requirements. The in-plane tensile strength of the energy storage material reaches 120MPa, mainly borne by the basalt fiber layer, which is slightly inferior to the carbon fiber plate of the same thickness but higher than the strength of the aluminum alloy cover. Energy storage performance: The internal 12 lithium polymer batteries form a 14.8V, 15Ah battery pack. The measured discharge capacity reaches 14.5Ah, which is close to the nominal value and can continuously power the device for about 10 hours (under the condition of power consumption of 20W). After 100 charge and discharge cycles, the capacity retention rate is above 98%, and the voltage of each cell remains balanced (maximum difference 0.03V), indicating that the management module balancing strategy is effective. Environmental adaptability: At a low temperature of -20°C, the battery can output about 80% of its capacity; after being stored at a high temperature of 60°C for 72 hours, there is no obvious attenuation of the cover structure and battery performance. No abnormal leakage current was found in the leakage monitoring of the conductive shielding layer, proving that the electrical insulation is complete. In terms of economy, this structure uses cheap fibers and resins, and the material cost is about 40% of the carbon fiber solution, and it has the potential for large-scale application. Example 3 embodies the application of the present invention to low-cost, large-capacity energy storage structural parts, which can be used in outdoor energy storage power supply housings, new energy equipment cabinets, etc., taking into account both structural support and power supply functions.
[0090] Example 4
[0091] In this embodiment, a 1mm thick composite of carbon fiber and aramid fiber is used as the load-bearing panel. The matrix is a modified epoxy resin, and the core material is embedded in a new solid-state lithium battery cell. The battery is 3mm thick and consists of a lithium metal negative electrode, a solid electrolyte, and a composite positive electrode. It is encapsulated in an aluminum-plastic film, measuring 100mm × 100mm × 3mm. The nominal voltage of the single cell is 3.7V, the capacity is 2Ah, and the thickness is 0.5mm. A thin layer of aramid paper is 0.5mm thick and provides insulation and cushioning. The carbon fiber provides the primary load-bearing capacity, while the aramid fiber blend improves the fracture toughness of the laminate and provides electrical isolation. The solid-state lithium battery uses a solid electrolyte instead of a traditional liquid electrolyte, which is non-flammable and heat-resistant, making it suitable for use as a structurally integrated energy storage unit. The optical fiber temperature sensor is a 0.25mm diameter bare fiber coated with a temperature-sensitive coating. This combination is designed to provide a higher safety factor, preventing the battery from catching fire or leaking even in severe impact or high-temperature environments, while maintaining overall performance similar to that of traditional carbon fiber composites.
[0092] like Figure 4As shown, the composite material is a curved panel structure suitable for use in car roofs or drone fuselages, employing a sandwich configuration with embedded energy storage cells. Between the upper and lower panels 23 are two layers of solid-state battery cells 24, eight per layer, with the upper and lower layers staggered. Thin layers of aramid paper 25 separate the battery cells 24 and the panels 23. A small piece of copper foil serves as a busbar 26 atop each battery cell 24. An intelligent management chip 27 is connected to each battery cell 24 via thin cables. A ring of fiber-optic temperature sensors 28 is embedded around the curved panel's frame.
[0093] T700-grade carbon fiber and Kevlar 49 aramid fiber were selected and woven into a plain blended fabric with 70% carbon fiber warp and 30% aramid weft. The fabric was cut slightly larger than the flattened dimensions of the final curved panel and cut into corresponding fan-shaped sections according to the required curvature. The fabric was manually preformed on a curved mold, with complex curvatures cut and overlapped to produce a dry fiber preform that conformed to the target surface. A small amount of spray adhesive was used to secure the layers to prevent shifting during subsequent operations, resulting in panel 23.
[0094] The battery cells 24 are placed in their designed positions on the lower woven fabric preform, located on the inner surface of the lower faceplate 23. Because the curved faceplate has a certain curvature, a temporary fixture is used to slightly bend the battery cells 24 to fit the fiber layer. Each battery cell is wrapped with a thin layer of foam tape to prevent direct contact between the edges of the cells and the carbon fiber. A 10mm gap is left between the battery cells 24 and between the cells 24 and the edge of the panel to be filled with a thin layer of aramid paper 25. Pre-cut thin layers of aramid paper 25 are inserted into these gaps and placed over the cells 24 as a barrier. A small piece of copper foil is placed on top of each battery cell as a busbar 26. This is connected to the copper foil of adjacent battery cells 24 with wires, forming a 4-series x 4-parallel network. The solder joints are located at the intersection of the copper foil and the wires, away from the battery packaging surface to prevent localized heat effects. After soldering, thin Kapton tape is used to provide insulation. A flexible intelligent management chip 27 is connected to the copper foil lead-out terminals of each battery cell 24 via flexible flat cables, which are laid and secured along the thin layer of aramid paper 25. Laying fiber optic temperature sensing lines 28: Attach fiber optic temperature sensing lines 28 with distributed temperature sensing capabilities along the four edges of the curved panel, surround each battery unit 24 in a grid pattern, and then lead out to a corner of the panel to connect to the demodulator.
[0095] On top of the battery assembly, the upper layer of hybrid fabric preform is laid, aligning the fiber direction and curvature. The entire stacking sequence from outside to inside is: hybrid fiber layer (outer surface) / cured resin film / several layers of carbon-aramid hybrid fabric / solid-state battery + aramid paper interlayer / several layers of carbon-aramid hybrid fabric / film / hybrid fiber layer (inner surface). The assembled laminate is placed in a vacuum bag, and the ply is strictly controlled to prevent wrinkles, and then cured in an autoclave according to the curing specifications of the modified epoxy resin: first vacuum evacuate to -0.09MPa to expel the air, then pressurize to 0.5MPa, slowly raise the temperature to 130°C and keep warm for 3 hours before cooling with the furnace. During this process, the solid-state battery structure is highly stable, and no leakage or damage occurs.
[0096] After curing, the vacuum bag is removed and the curved composite board is taken out. Trim and punch holes to meet the design dimensions and installation requirements. Check the inner surface to ensure that each solid-state battery is firmly embedded and the surface resin is flat and free of bubbles. Connect the optical fiber temperature sensing line 28 to the demodulation equipment to perform a uniform heating test on the board. The temperature distribution fed back by the optical fiber is consistent with the thermocouple measurement, proving that the optical fiber is well embedded. Enable the intelligent management chip 27, and the voltage of each battery is around 3.7V after power-on test. The internal resistance is measured at an average of 50mΩ, with no abnormalities. The serial-to-parallel conversion is tested through chip commands (the internal resistance of solid-state batteries is large, so they are generally fixed to series supply high voltage. Only the switching function is tested here). It is found that the high-voltage mode (4 strings) outputs 14.8V, and the low-voltage mode (2 strings and 2 parallels) outputs 7.4V, the capacity doubles to 8Ah, and the switching process is smooth. Finally, the panels were subjected to mechanical performance tests, including applying design loads (such as standard loads on a car roof) under simulated installation boundary conditions. The deflection and strain of the panels were in line with expectations and were almost the same as those of carbon fiber panels without embedded batteries, indicating that embedding solid-state batteries did not weaken the structural strength.
[0097] In this example, the resulting curved structural panel weighs approximately 3.5 kg, of which the solid-state battery portion weighs approximately 1 kg. Its safety performance is particularly outstanding: needle penetration and high-temperature extreme tests revealed that once a solid-state battery cell was punctured, it only experienced short-circuit heating and slight swelling, with no fire or explosion. Adjacent cells remained intact. After the panel was placed in a 150°C environment for 2 hours, the battery exhibited no leakage, with only a slight performance degradation that could be recovered. Mechanical Properties: The panel achieved a tensile strength of 600 MPa and a flexural modulus of approximately 55 GPa, comparable to pure carbon fiber / epoxy panels with the same number of layers. This is due to the thin, flat solid-state battery cells, which have minimal impact on the laminate and are strongly bonded to the surrounding resin through co-curing, acting to some extent as a thickening agent similar to a foam core. Electrochemical Performance: The total capacity is 8 Ah, with 7.5 Ah discharged at 0.5C (4A) (93% utilization), and an average discharge voltage of 12.8 V. While the high-rate performance of the solid-state battery is slightly inferior, it can reach 98% capacity at 0.2C. After 200 cycles, the capacity remains above 90%, and the internal impedance increases by 10%, which is presumably caused by the deformation of the carbon negative electrode. This attenuation rate is still significantly better than that of traditional lithium batteries (the absence of liquid electrolyte avoids the continuous growth of SEI). Intelligent monitoring: The optical fiber sensing network can provide real-time temperature field within the board: when 2C charge and discharge are repeated, the highest temperature point is located in the central battery, reaching 55°C, and the others are below 50°C; the edge temperature of the board is as low as about 40°C. This full-field perception helps to optimize thermal management. In general, Example 4 reflects the application of the structure of the present invention in extremely high safety scenarios. By adopting solid-state batteries and carbon / aramid hybrid materials, the structural energy storage device can still perform reliably under strict environmental and safety requirements.
[0098] Example 5
[0099] In this embodiment, an intelligent structure with multiple energy storage units and multiple sensing functions is integrated through advanced manufacturing technology. Continuous carbon fiber 3D printing and co-curing process are used to prepare special-shaped structural parts. The material is nylon resin reinforced by carbon fiber + aramid fiber hybrid. Two energy storage units (lithium-ion battery and supercapacitor hybrid) and multi-type sensor networks are embedded to achieve both high energy density and high power density, and can fully monitor structural loads, vibrations, and impacts. The material selection of this embodiment takes into account: nylon resin has good toughness and is easy to 3D print, continuous carbon fiber filaments increase stiffness, and aramid short fiber hybrids provide insulation and crack resistance; the combination of lithium battery + supercapacitor can meet different power requirements; multi-sensor fusion improves the degree of intelligence. This solution is suitable for use as a drone fuselage or automobile body module, etc., which requires components with complex shapes and highly integrated functions.
[0100] like Figure 5As shown, the structural member of Example 5 is shaped like a hollow rectangular beam 29, with energy storage cavities arranged in sections along the length. A battery module cavity 30 is provided in the thicker middle section of the hollow rectangular beam 29, embedded with eight 21700 lithium-ion battery cells 31 (specifications: single cell 4Ah, 3.7V); supercapacitor module cavities 32 are provided in the thinner front and rear sections of the hollow rectangular beam 29, each embedded with six small supercapacitor modules 33 (2.7V 50F capacitors, 20mm diameter). The battery cells 31 are connected in parallel with 4 in series, while the supercapacitor modules 33 are all connected in series. The lead wires of each module are connected to the central intelligent energy management unit 35 via copper foil traces 34 embedded in the wall. The central intelligent energy management unit 35 is located outside the middle section of the hollow rectangular beam 29. Multiple strain gauges 36 are embedded in the key connection ends of the hollow rectangular beam 29 to monitor the load. Accelerometers 37 are embedded in the beam wall of the hollow rectangular beam 29, and each battery cell 31 is affixed with a voltage and temperature monitoring module 38. All sensors are connected to the central intelligent energy management unit 35.
[0101] Using a large-scale continuous fiber-reinforced 3D printer, the hollow rectangular beam 29 is printed layer by layer according to the CAD model. The printing materials are carbon fiber-reinforced nylon (continuous fiber) and aramid fiber-reinforced nylon (a blend of short fibers). During the printing process, the fiber layout is controlled: continuous carbon fiber bundles (applied via a coextrusion nozzle) are embedded in each shell wall along the axial direction of the hollow rectangular beam 29. A surrounding fiber loop is added near the battery module cavity 30 for reinforcement. At the same time, 10% chopped aramid fiber is evenly mixed into the nylon matrix to improve toughness and insulation. During printing, slots and through-holes matching the components are printed in the battery module cavity 30 and the capacitor module cavity 32. Small inserts or slots are embedded near the predetermined sensor locations during printing to facilitate the subsequent installation of strain gauges 36 and accelerometers 37. After printing is completed, the resulting hollow beam blank is integrated with the module cavities and wiring channels.
[0102] Insert the battery cells 31 into the cylindrical slots of the battery module cavity 30 in the middle section in sequence, with 4 cells in each row, and two rows stacked up and down to form a 2-parallel × 4-series layout. Each battery is wrapped with a layer of polyolefin heat-shrinkable insulation film. Insert the copper foil wiring 34 into the groove reserved for printing, connect the batteries in 4 series and weld them, connect the parallel parts with thick copper busbars, and finally lead out the positive and negative poles at both ends. Fill the gaps between and around the batteries with flame-retardant foamed silicone to fix them. In the front and rear sections of the hollow rectangular beam 29, the 6 supercapacitor modules 33 are respectively embedded in the corresponding cavities, connected into a module with thick wires in a full series manner, and the package is also filled with foam glue to fix it. All the lead-out positive and negative lines are gathered to the installation position of the management unit.
[0103] The customized central intelligent energy management unit 35 is fixed to the flat area of the outer wall of the middle section of the hollow rectangular beam 29 and connected to the internal battery and supercapacitor lead wires via screws and wires. The unit includes a microcontroller, a bidirectional DC-DC converter (for transferring energy between the lithium battery and the supercapacitor), a wireless communication module, and a sensor interface. Subsequently, a strain gauge 36 is installed in the embedded position of the printed part (adhesively attached to the inner wall of the beam end), and its lead wires are connected to the management unit; the accelerometer 37 module is placed in the reserved slot and sealed with glue, and then connected to the unit; the voltage and temperature monitoring module 38 (a small PCB with a thermistor and voltage divider) for each lithium battery is attached to the top of the battery and connected to the unit; the voltage sensing wire of the supercapacitor is also connected to the unit. After completing all connections, a comprehensive electrical inspection and sensor signal test are performed to ensure that there are no short circuits and the sensor readings are normal.
[0104] The beam structure with installed components undergoes a complete co-curing and encapsulation process. Localized heating is employed: an electric heating film is applied to the beam surface, heating only the shell to 240°C for 30 minutes. Internally circulating cooling air protects the battery capacitors from overheating. After co-curing, the shell layers are more tightly bonded and the fiber-resin interface is optimized. Subsequently, the exposed portion of the central intelligent energy management unit 35 is coated with waterproof conformal coating, the beam openings are sealed, and a weather-resistant coating is sprayed onto the surface, completing the final component.
[0105] The hollow beam structure of Example 5 weighs about 4.0kg, of which the energy storage element is about 1.5kg and the structure body is 2.5kg. Mechanical properties: According to finite element analysis, the beam can be used as the main beam of the UAV fuselage, withstanding a maximum bending stress of 140MPa under flight load, with a safety margin of >1.5; the actual three-point bending test measured the beam's deflection of 2.5mm under a load of 1kN, showing approximately isotropic stiffness, which is the result of optimized laying of continuous fiber 3D printing. Energy storage performance: The total energy of the lithium battery module is approximately (8×3.7V×4Ah)=118Wh, and the energy of the supercapacitor module is approximately (6×2.7V, 50F)=1 / 2CV^2≈1 / 25016.2^2=6564J≈1.82Wh, but its advantage lies in high power output. Through coordination by the intelligent management unit, the following functions are achieved: During stable power supply, the lithium battery module primarily outputs power. During moments of high current demand (such as drone takeoff), the supercapacitor module is instantly connected in parallel to provide additional current, with a peak power of up to 3kW, to maintain the battery current within a safe range. During regenerative energy recovery (such as when the drone glides or the vehicle decelerates), the supercapacitor module prioritizes energy absorption for rapid charging, then slowly transfers the energy to the battery for storage. Tests show that under a continuous discharge of 20A, the lithium battery temperature rises to 45°C and the supercapacitor temperature rises to 40°C, both within safe limits. Sensor monitoring data shows that under simulated flight vibration conditions (±5g random vibration), the structural strain peaks at 300με. The signals captured by the strain gauge 36 and accelerometer 37 are consistent with the flight load model, demonstrating the effectiveness of structural health monitoring. In the event of an impact (simulating a fall with a peak acceleration of 20g), the management unit automatically disconnects the battery output and sends an emergency signal. Comprehensive Performance: This intelligent beam structure achieves a combination of high specific energy (approximately 47 Wh / kg) and high specific power (peak 750 W / kg), and possesses autonomous sensing and protection capabilities, while reducing weight by over 15% compared to traditional designs. Example 5 fully demonstrates the advantages of this invention in complex structures, hybrid energy storage, and highly intelligent applications, demonstrating that through 3D printing and multifunctional integration, structural energy storage composite materials can be expanded to a wider range of engineering fields.
[0106] As can be seen from the above embodiments, the present invention provides an embedded structural energy storage integrated composite material and a method for preparing the same. The embedded structural energy storage integrated composite material provided by the present invention offers flexibility and advancements in structural design, electrical connection methods, material combinations, and intelligent integration. While different embodiments select corresponding materials and processes for different application requirements, all embody the core concept of the present invention: organically embedding energy storage elements within a composite load-bearing structure and achieving functional integration.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. An embedded structure energy storage integrated composite material, characterized in that: It consists of a composite plate with a sandwich structure and an energy storage unit and a sensing unit embedded therein; The composite board includes a functional layer, a load-bearing layer and a surface layer; The functional layer includes an electrically insulating inner core, a plurality of independent energy storage units are embedded in the internal pores of the electrically insulating inner core, a bearing layer is arranged on both sides of the electrically insulating inner core, and the outer side of the bearing layer is a surface layer; The energy storage units are electrically connected via embedded flexible circuits, which are arranged along the surface and / or inside of the electrically insulating inner core, connecting the electrodes of each energy storage unit and integrating a smart chip; The sensing unit is a sensor network arranged inside the composite material, and the sensor network is obtained by connecting sensors, flexible circuits and smart chips.
2. The embedded structure energy storage integrated composite material according to claim 1, characterized in that: The electrical insulation inner core is in a honeycomb or grid shape.
3. The embedded structure energy storage integrated composite material according to claim 1 or 2, characterized in that: The load-bearing layer is a laminated structure, including a fiber layer and a resin matrix; The surface layer is a laminated structure, including a fiber prepreg layer or a fiber fabric layer.
4. The embedded structure energy storage integrated composite material according to claim 3, characterized in that: The materials of the electrical insulation core, fiber layer, fiber prepreg layer and fiber fabric layer independently include one or more of carbon fiber, aramid fiber and basalt fiber; The resin matrix includes one or more of polyimide resin, FEP resin, epoxy resin and polyester resin.
5. The embedded structure energy storage integrated composite material according to claim 1 or 4, characterized in that: The sensing unit is used to collect structural stress, strain distribution, vibration impact events or parameters of each energy storage unit.
6. The embedded structure energy storage integrated composite material according to claim 1, characterized in that: The sensor includes one or more of a MEMS piezoelectric sensor, a temperature sensor, a humidity sensor, a voltage sensor and a fiber grating sensor.
7. The embedded structure energy storage integrated composite material according to claim 1, characterized in that: The smart chip includes a functional circuit of a battery management system and an optical fiber sensing module, which is used to detect the status of the energy storage unit and implement energy management strategies and safety measures.
8. The method for preparing the embedded structure energy storage integrated composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1) preparing an electrically insulating inner core and embedding the energy storage unit therein and fixing it; Step 2) Arrange the flexible circuit and smart chip and integrate their electrical connection network on the electrically insulating core or panel; Step 3) Lay out the panels and embed the sensors between the designated layers during assembly; Step 4) The composite materials are laminated and assembled, and then cured and formed to obtain an integrated structural energy storage composite plate. After post-processing, an embedded structural energy storage integrated composite material is obtained.
Citation Information
Patent Citations
Structural energy storage assemblies and methods for production thereof
US20160330842A1
Cited By
Optical fiber sensing-capacitor energy storage-composite material integrated structure and forming method thereof
CN121498757A
Embedded structure battery and preparation method thereof
CN121885909A
Supporting piece, preparation method thereof and electronic equipment
CN122018645A